Leaf carbohydrate metabolic enzyme activities are associated with salt tolerance and yield stability in the climate-resilient crop Camelina sativa - Peter Stasnik; Johann Vollmann; Dominik K. Großkinsky; Claudia Jonak (Plant Stress, 2024)
Soil salinity is an increasingly severe problem affecting plant growth and development thus posing a threat to agricultural production worldwide. Many crops currently grown are susceptible to even moderate salt stress, and crop diversification is sought to cope with increasingly challenging environmental conditions. Camelina sativa is a versatile, underutilized, low-input Brassicaceae oilseed crop valued for its high-quality seeds and its resilience to a wide range of climate conditions. In this study, the effects of salt stress on the growth and productivity of two camelina cultivars and six landraces from different geographic regions were examined. The performance of these lines was related to adjustments in their carbohydrate metabolic enzyme activity profiles in leaves as a central physiological hub. Profiling enzyme activities and their regulation in response to salt stress revealed significant genotype × treatment (G × T) interactions and allowed the identification of specific activity signatures associated with differences in yield stability in the tested lines. Yield-stable landraces showed distinct regulation patterns contrasting those of less yield-stable lines. In particular, upregulation of specific enzyme activities was associated with yield stability under salt stress. Camelina landraces may be promising resources to improve tolerance to salinity, with plasticity in carbohydrate metabolism as a contributing mechanism. Overall, these results provide a valuable basis for enzyme activity signatures as new physiological markers for supporting breeding programmes.